Sistem Informasi Manajemen pada PT. Buyung Putra Pangan Berbasis Web - Agustian Hartony; Muhammad Rachmadi (Syntax Corporation, 2023)
On a business trip at PT. Buyung Putra Pangan is still constrained by recording data on rice sales and rice production results every month which is done manually using a book, so it is difficult for the manager or secretary to see the recording of rice sales data and production results in the book directly if outside the office. So that there are no errors in recording data on the results of production, purchase, production and sales of rice. The system can make it easier for managers to monitor performance in doing business at PT. Buyung Putra Pangan. The method used is the RUP (Rational Unified Process) method, which is a software development method that is carried out iteratively, focuses on architecture (architecture-centric), is more directed based on use cases (use case driven). The design is built to display a management information system that can be used by users by using Use Case Diagrams to build a system for recording data on sales, purchases and rice production data. This application can help the Admin to manage the data contained in the website application, the Manager can see the recording of rice being moved from one place to another and the Manager can see the results of reports from rice sales and production in detail because they can find out the total sales per day and per month.